(untitled) (Regional aspects of productive forces development of Ukraine, 2023)
Introduction. In a globalized world, foreign economic processes have a significant impact on the state of the national economy. The level of integration into global value chains changes the level of development of the business environment and the structure of the economy. The publication analyzes Ukraine’s international trade activity in 2018-2021 and its current state. Ukrainian companies ensure integration into global value chains. However, the low degree of processing of export-oriented goods remains a significant problem. The study of current trends in Ukraine’s foreign economic activity is relevant for overcoming current challenges and identifying key growth priorities. Purpose. The aim of the article is to study the volume and structure of export-import operations and foreign trade processes of the Ukrainian economy within the framework of global value chains (GVC). Research methods. The article uses the methods of analysis and synthesis, systematization and generalization, abstraction, data presentation, and formal logic. Results. The study confirms the positive dynamics of Ukraine’s foreign trade in 2018-2021. Ukrainian companies export mainly low value-added goods and import high value-added goods. The development of Ukraine’s economy requires successful integration into global supply chains. This is possible if we move from exporting raw materials to increasing the volume and depth of their processing in the national economy, and further exporting high value-added goods. The study showed that economic relations between Ukraine and its trading partners demonstrate a significant increase in foreign trade within global value chains. Ukrainian companies are involved in the development of global integration processes mainly in sectors that consume agricultural products, metallurgy, and IT-services. Agricultural and industrial products exported from Ukraine account for about 40% of total international sales. Against the backdrop of Russia’s full-scale military invasion, a negative trend is the decline in Ukraine’s foreign trade turnover by almost 30% (exports by 35% and imports by 25%). The largest decline in exports occurred in the metallurgical and chemical industries. The share of agricultural products in exports increased, while the share of fuel, equipment, and vehicles in imports increased. Conclusion. Foreign economic activity determines the business activity of business entities, their integration into the system of international economic relations, and creates essential preconditions for the transformation of the national economy, improving the living conditions and living standards of the population. Ukrainian exports are dominated by a high share of intermediate goods used as raw materials for the production of other final consumer goods. Therefore, it is advisable to stimulate deep processing of raw materials in the domestic market, the finished products of which can become competitive on the foreign market. With Ukraine’s integration into global and regional business services in the context of global value chains, it is possible to ensure positive effects from foreign economic activity. The basis for successful integration into global value chains is to stimulate the development of international cooperation between enterprises on global business platforms, as well as local innovation ecosystems that will facilitate the creation of innovative industries, both through public and private investment.